MIRA project self-evaluation - Rodriguez Clemente R. (Moving forward in the Euro-Mediterranean Research and Innovation partnership. The experience of the MIRA project, 2013)
This article describes the background, development and lessons learnt of INCO-Net Project MIRA, aimed at supporting the Euro-Mediterranean cooperation in the field of Research and Innovation.